Role of Supreme Audit Institutions in Governments' Response to COVID-19 : Emergency and Post Emergency Phases - World Bank (World Bank, Washington, DC, 2020)
Coronavirus disease 2019 (COVID-19) is an unprecedented public health emergency, with associated significant economic impact, affecting all developing and developed countries. As it unfolds and countries respond, the role of Supreme Audit Institutions (SAIs) is being recognized as crucial to supporting the government response mechanisms through maintaining public financial management discipline and ensuring transparency and accountability. Past experience from SAIs' engagement in government responses to natural and human-made disasters, including health emergencies like Ebola, provides good lessons for SAIs confronted with the COVID-19 pandemic. This note seeks to propose ideas on how SAIs can respond to the crisis now and during the recovery phase. During the emergency stage, the primary focus of governments is on safeguarding livelihoods and public health. Auditors are themselves constrained both by their physical access limitations and the imperative to avoid impeding government's speedy responses to the pandemic. Under these circumstances, crucial oversight and key controls may suffer, especially as public financial management systems are adapted to be responsive and flexible.